PENERAPAN ACTIVE, JOYFUL AND EFFECTIVE LEARNING (AJEL) BERBASIS BIOEDUTAINMENT MATERI PERUBAHAN LINGKUNGAN - Choirunnisa, Iffa Faiza; Irsadi, Andin (Journal of Biology Education, 2014)
Abstract _________________________________________________________________ The aim of the research was to analyze the effect of the application of Active, Joyful and Effective Learning (AJEL) with bioedutainment strategy based on activity and learning outcomes of students in class X of MAN Kendal. Sample was collected by a purposive sampling technique with two experimental classes, namely class X 4 and X 6, whereas X 5 as control class. This study was a Quasi Experimental Design with Non-Randomized Control Group Pretest-Posttest Design. Components of learning model that reflects the Active, Joyful and Effective Learning (AJEL) with bioedutainment strategy that used in this research was time token, outdoor learning, and gallery walk. Data were analyzed quantitatively. Tests using the t test showed the difference in the value of pretest-posttest experimental class is larger than the control class. The results of tests n-gain analysis of student learning outcomes obtained experimental class higher than the control class. Learning is effective because the classical >75% of students achieving KKM, student activity> 75% and questionnaire responses of students >75% said that learning are fun and not boring. Â Abstrak ___________________________________________________________________ Penelitian ini bertujuan untuk menganalisis pengaruh penerapan Active, Joyful and Effective Learning (AJEL) berbasis bioedutainment terhadap aktivitas dan hasil belajar siswa kelas X MAN Kendal. Sampel penelitian diperoleh dengan teknik purposive sampling dengan dua kelas eksperimen yaitu kelas X4 dan X6, satu kelas kontrol X5. Penelitian ini merupakan penelitian Quasi Experimental Design, dengan pola Non-randomized Control Group Pretest-Posttest Design. Komponen model pembelajaran yang mencerminkan Active, Joyful and Effective Learning (AJEL) berbasis bioedutainment yang digunakan pada penelitian ini adalah time token, outdoor learning, dan gallery walk. Data dianalisis secara kuantitatif. Pengujian menggunakan uji t menunjukkan selisih nilai pretest-posttest kelas eksperimen lebih besar dari kelas kontrol. Hasil analisis uji n-gain hasil belajar siswa kelas eksperimen lebih tinggi daripada kelas kontrol. Pembelajaran dikatakan efektif karena secara klasikal >75% siswa mencapai KKM, aktivitas siswa >75% dan angket tanggapan siswa >75% menyatakan pembelajaran menyenangkan dan tidak membosankan.